Development of an integrated e-health tool for people with, or at high risk of, cardiovascular disease: The Consumer Navigation of Electronic Cardiovascular Tools (CONNECT) web application. (December 2016) - Neubeck, Lis; Coorey, Genevieve; Peiris, David; Mulley, John; Heeley, Emma; Hersch, Fred; Redfern, Julie
Abstract: Background: Cardiovascular disease is the leading killer globally and secondary prevention substantially reduces risk. Uptake of, and adherence to, face-to-face preventive programs is often low. Alternative models of care are exploiting the prominence of technology in daily life to facilitate lifestyle behavior change. Objective: To inform the development of a web-based application integrated with the primary care electronic health record, we undertook a collaborative user-centered design process to develop a consumer-focused e-health tool for cardiovascular disease risk reduction. Methods: A four-phase iterative process involved ten multidisciplinary clinicians and academics (primary care physician, nurses and allied health professionals), two design consultants, one graphic designer, three software developers and fourteen proposed end-users. This 18-month process involved, (1) defining the target audience and needs, (2) pilot testing and refinement, (3) software development including validation and testing the algorithm, (4) user acceptance testing and beta testing. From this process, researchers were able to better understand end-user needs and preferences, thereby improving and enriching the increasingly detailed system designs and prototypes for a mobile responsive web application. Results: We reviewed 14 relevant applications/websites and sixteen observational and interventional studies to derive a set of core components and ideal features for the system. These included the need for interactivity, visual appeal, credible health information, virtual rewards, and emotional and physical support. The features identified as essential were: (i) both mobile and web-enabled 'apps', (ii) an emphasis on medication management, (iii) a strong psychosocial support component. Subsequent workshops ( n  = 6; 2 × 1.5 h) informed the development of functionality and lo-fidelity sketches of application interfaces. These ideas were next tested in consumer focus groups ( n  = 9; 3 × 1.5 h). Specifications for the application were refined from this feedback and a graphic designer iteratively developed the interface. Concurrently, the electronic health record was linked to the consumer portal. A written description of the final algorithms for all decisions and outputs was provided to software programmers. These algorithmic outputs to the app were first validated against those obtained from an independently programmed version in STATA 11. User acceptance testing ( n  = 5, 2 × 1.0 h) and beta testing revealed technical bugs and interface concerns across commonly-used web browsers and smartphones. These were resolved and re-tested until functionality was optimized. Conclusion: End-users of a cardiovascular disease prevention program have complex needs. A user-centered design approach aided the integration of these needs into the concept, specifications, development and refinement of a responsive web application for risk factor reduction and disease prevention.